A Walk in the Park: Kinesthesia in the Arts of Landscape - Pashman, Susan, (Religious Studies, Theology and Philosophy E-Books Online, Collection 2024., 2024)
Current neuroscience discloses that all emotional feeling originates as movement. Kinesthesia, our sixth sense, begins with movement of muscle cells and ends as emotion. Depth perception, which depends on movement, is always feeling-laden. To be expressive, art must somehow move our bodies. Studies of expressive dance demonstrate that we unconsciously model observed movements, duplicating in ourselves the feelings that generated the dancer's movements. The art of landscape creates choreography for a walk. But each of the fine arts play a role in landscape design. Here, then, is a new theory of landscape that easily extends to all the fine arts, explaining our enjoyment in landscape, as well as aesthetic enjoyment more generally.